Abusir : the necropolis of the sons of the sun - Verner, Miroslav (The American University in Cairo Press, 2018)
This work documents the uncovering, by a team of Czech archaeologists, of a hitherto neglected wealth of ancient remains dating from the Old Kingdom to the Late Period. This is Abusir, realm of Osiris, God of the dead, which lies at the centre of the pyramid field of the Memphite necropolis